Compressive mechanical properties of HTPB propellant at low, intermediate, and high strain rates. Issue 23 (24th February 2016) - Yang, Long; Xie, Kan; Pei, Jiangfeng; Sui, Xin; Wang, Ningfei
ABSTRACT: Low, intermediate, and high strain rate compression testing (1.7 × 10 −4 to 2500 s −1 ) of the hydroxyl‐terminated polybutadiene (HTPB) propellant at room temperature, were performed using a universal testing machine, a hydraulic testing machine, and a split Hopkinson pressure bar (SHPB), respectively. Results show that the stress linearly increases with strain at each condition; the increasing trend of stress at a given strain with the logarithm of strain rate changes from a linear to an exponential form at 1 s −1 . By combining these characteristics, we propose a rate‐dependent constitutive model which is a linearly elastic component as a base model, then multiplied by a rate‐dependent component. Comparison of model with experimental data shows that it can characterize the compressive mechanical properties of HTPB propellant at strain rates from 1.7 × 10 −4 to 2500 s −1 . © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43512. Abstract :